2020
DOI: 10.1111/hex.13068
|View full text |Cite
|
Sign up to set email alerts
|

The revised Patient Perception of Patient‐Centeredness Questionnaire: Exploring the factor structure in French‐speaking patients with multimorbidity

Abstract: Background The Patient Perception of Patient‐Centeredness (PPPC) questionnaire was revised, and there is a need for the questionnaire to be tested in diverse primary care populations. Objectives This study aimed to examine the factor structure of the Revised PPPC questionnaire (PPPC‐R) in French‐speaking patients with multimorbidity. Design Secondary analysis from baseline data of the French arm of Patient‐Centered Innovations for Persons with Multimorbidity Study (PACEinMM Study). Setting and participants Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
4
5
2
Order By: Relevance
“…Compared with the results from Ryan et al, [9] F1 in our results contained most items under the component of "health, disease, and the illness experience", except item 11, which is item 8 in the 18-item PPPC-R scale. Other items stayed consistent with the results from Ryan et al Our results also aligned with ndings from testing the 18-item scale used by Nguyen et al [4] in the primarily Francophone areas in Canada. From patients' perspective, components 1 and 2 (exploring health, disease, and the illness experience; understanding the whole person) may be closely related and necessary during appointments with physicians, and learning the causes and development of diseases is a mandatory procedure.…”
Section: Comparison With Previous Scalessupporting
confidence: 90%
See 1 more Smart Citation
“…Compared with the results from Ryan et al, [9] F1 in our results contained most items under the component of "health, disease, and the illness experience", except item 11, which is item 8 in the 18-item PPPC-R scale. Other items stayed consistent with the results from Ryan et al Our results also aligned with ndings from testing the 18-item scale used by Nguyen et al [4] in the primarily Francophone areas in Canada. From patients' perspective, components 1 and 2 (exploring health, disease, and the illness experience; understanding the whole person) may be closely related and necessary during appointments with physicians, and learning the causes and development of diseases is a mandatory procedure.…”
Section: Comparison With Previous Scalessupporting
confidence: 90%
“…[1] The quality of patient-centered care improvement has been associated with various positive health system outcomes, such as effectively enhanced patient satisfaction, improved health-related outcomes(e.g., improvement of symptoms), reduced avoidable referrals, and diagnostic costs. [2][3][4][5][6] If the provider bridges the gap between clinical quality and patient perception, it could improve medical utilization and clinical quality. [7] Mohammed's systematic review found that patients can perceive ten domains of patient-centered care quality (communication, access, shared decision making, provider knowledge and skills, physical environment, patient education, electronic medical record, pain control, discharge process, and preventive services).…”
Section: Introductionmentioning
confidence: 99%
“…Similar experiences were found with the Patient-Centered Clinical Method (PCCM) questionnaire in Canada, where the complexity of multimorbidity and associated factors can be comparable. 30 There are even other analyses comparing ways of approaching multimorbidity, which suggests that hierarchical cluster analysis shows comorbidity, while exploratory factor analysis multimorbidity. 31 Subsequent analyses can use this approach to build scales of risk of death and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants are younger and more educated than the participants of other studies examining the factor structure of the scale. 11,18 Due to their age, our population probably was considerably different with respect to health problem profile and consequent primary care use, especially from the study examined French version in which the item had the highest factor load. For young and educated people who have few health problems and probably use primary care seldomly, the physicians' knowledge of their family life may be meaningless in the context of receiving health care.…”
Section: Discussionmentioning
confidence: 97%